2017
DOI: 10.1200/jco.2016.67.5140
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Examined Lymph Node Count on Precise Staging and Long-Term Survival of Resected Non–Small-Cell Lung Cancer: A Population Study of the US SEER Database and a Chinese Multi-Institutional Registry

Abstract: PurposeWe investigated the correlation between the number of examined lymph nodes (ELNs) and correct staging and long-term survival in non–small-cell lung cancer (NSCLC) by using large databases and determined the minimal threshold for the ELN count.MethodsData from a Chinese multi-institutional registry and the US SEER database on stage I to IIIA resected NSCLC (2001 to 2008) were analyzed for the relationship between the ELN count and stage migration and overall survival (OS) by using multivariable models. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
253
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(272 citation statements)
references
References 26 publications
(17 reference statements)
5
253
2
1
Order By: Relevance
“…However, the accuracy of pN stage is also impacted by various factors. Adequate numbers of stations and LNs need to be collected during surgery, correctly labeled, and sent for pathological examination . In the pathological laboratory, the LNs of various stations should be routinely examined, including intrapulmonary LNs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the accuracy of pN stage is also impacted by various factors. Adequate numbers of stations and LNs need to be collected during surgery, correctly labeled, and sent for pathological examination . In the pathological laboratory, the LNs of various stations should be routinely examined, including intrapulmonary LNs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Liang et al reported data from a Chinese multiinstitutional registry and the US SEER database on stage I to IIIA resected NSCLC [2001][2002][2003][2004][2005][2006][2007][2008]; in this paper, a larger number of examined LNs was associated with more-accurate node staging and better long-term survival. The authors recommended 16 LNs as the cut point for evaluating the quality of LN examination and declaring a node-negative disease (22). However, the data of the stations of dissected LNs was not available in that publication.…”
Section: Discussionmentioning
confidence: 99%
“…For patients undergoing lobectomy for NSCLC, accumulating data have demonstrated that a greater number of harvested LNs is associated with improved survival (10,11). Normally, only patients with node-negative disease in preoperative clinical staging are deemed to be suitable candidates for segmentectomy.…”
Section: Introductionmentioning
confidence: 99%